(untitled) (mathematica didactica, 2017)
Concrete Art is a genre whose works exhibit a particular relation to mathematics with regards to content: number series, elements of combinatorial analysis or geometry are frequently implemented as aesthetic patterns in these works of art. A mathematical analysis of these images may gradually expose such points of contact - and thus bears characteristics of both problem solving as well as mathematical modelling. An explorative field study of secondary school students (10th and 11th grade) and teachers investigated whether these connections, initially derived from theory, can be verified empirically.